Conservative Resectoscopic Surgery, Successful Delivery, and 60 Months of Follow-Up in a Patient with Endometrial Stromal Tumor with Sex-Cord-Like Differentiation - Pasquale De Franciscis; Flavio Grauso; Domenico Ambrosio; Marco Torella; Enrico Michelino Messalli; Nicola Colacurci (Case Reports in Obstetrics and Gynecology)
Uterine tumors with sex-cord-like differentiation are extremely rare types of uterine stromal neoplasm. These tumors were classified into two groups with considerable practical relevance because clinical behaviour of uterine tumor resembling ovarian sex cord tumor (UTROSCT) differs widely from its closely related endometrial stromal tumors with sex-cord-like elements (ESTSCLE). Treatment and prognosis of these tumors are unresolved issues because of the exiguous number of reported cases. We describe a rare case of endometrial stromal tumor with sex-cord-like differentiation successfully treated by resectoscopic surgery and conservation of the uterus, in an infertile patient affected by metrorrhagia. This procedure resulted in a pregnancy immediately after treatment and in a successful delivery. During 60 months of follow-up no evidence of recurrence was observed.